Feasibility of using carbon doped aluminium oxide co-doped with magnesium as a thermoluminescence dosimeter - Ainun Jariah Awang, 1989-, author 500933 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Doktor Falsafah (Fizik))